Role of Saturated Fatty Acid (SFA) for Degradation of Oil Quality - Firdausi, Ketut Sofjan (JURNAL SAINS DAN MATEMATIKA, 2015)
In this study, the phenomena of natural polarization has been used as a preliminary test of vegetable oil quality. The formation of saturated fatty Acid (SFA) has been studied as a most responsible parameter for degradation of oil quality related to its expired limitation. The Oil quality was indicated by change of light polarization, and was measured using pair of polarizer-analyser. The result shows that the change of polarization can be used to indicate oil quality level related to its expiration date. This method also shows predicted SFA formation and apparently it is relative more powerful than standard parameters such as free fatty acid (FFA) test and peroxide value (PV) test. For future, this method has provided good prospect to evaluate the existence of the halal level of oil due to lard (pig oil). Keywords: natural polarization, vegetable oil quality, saturated fatty acid (SFA)